A Study on Growth and Instability of Poultry Farms in Namakkal District (Tamilnadu) - Vetrivel, S. C; Mohanasundari, M (Journal of Commerce and Trade, 2011)
India is a developing country primarily has an agricultural economy. If agriculture blooms, the country prospers. Agriculture is a diversified subject covers such activities as farming, forestry, animal husbandry and fishery including agro- based industries in broader concept. Rural development improves the quality life of the weaker sections and gives way for participation and involvement of the masses in the process of decision making in economic and social life of and society.They provide livelihood to and million of rural house holds in the sub marginal level both land less and small landholders. They prove to be the best way to alleviate rural poverty and reduce income disparities. Industrial sector depends on agriculture for their raw material and allied products. Poultry and egg are popular food articles of high nutritional value and so and major break through have been achieved in egg production and broiler stock. This due to integrated development of breeding feeding, marketing, healthcare and nutrition etc. Poultry farming by providing additional income to the agricultures helps them to earn more and helps the nation to develop with out any wide disparities in the of income.